Serbia Public Sector Accounting Review : Report on the Enhancement of Public Sector Financial Reporting - World Bank Group (World Bank, Washington, DC, 2018)
The government’s public financial management (PFM) Reform Program 2016-2020 foresees the gradual transition of public sector financial reporting from a cash basis to an accrual basis of accounting and the application of International Public Sector Accounting Standards (IPSAS). This will significantly improve the quality of financial information and should enable better informed decision-making, more efficient use of public funds and resources and improved fiscal performance. This Report on the Enhancement of Public Sector Financial Reporting is one output of the Serbia Public Sector Accounting Reform Technical Assistance project funded by the Swiss State Secretariat for Economic Affairs (SECO) through the Strengthening Accountability and Fiduciary Environment (SAFE) Trust Fund under the Public Sector Accounting and Reporting Program (PULSAR) which provides support for the development and implementation of public sector accounting standards. This report supports the development of a plan towards that goal by assessing the institutional framework for public sector accounting as well as the gap between Serbian public sector generally accepted accounting principles (PS GAAP) and IPSAS.